CXCR5+CD8 T cells: Potential immunotherapy targets or drivers of immune-mediated adverse events? - Turner, Christi N.; Mullins, Genevieve N.; Hoyer, Katrina K. (Frontiers in Medicine, 2022)
CXCR5+CD8 T cells have attracted significant interest within multiple areas of immunology, cancer, and infection. This is in part due to their apparent dual functionality. These cells perform as cytotoxic cells in a variety of infection states including LCMV, HBV, HIV and SIV. However, CXCR5+CD8 T cells also associate with B cells in peripheral organs and function to stimulate B cell proliferation, antibody/B cell receptor class-switch, and antibody production. CXCR5+CD8 T cells are similar to CXCR5+CD4 T follicular helpers in their genetic make-up, B cell interactions, and functionality despite possessing elevated programmed cell death 1 and cytotoxic proteins. Within cancer CXCR5+CD8 T cells have risen as potential prognostic markers for overall survival and are functionally cytotoxic within tumor microenvironments. In inflammatory disease and autoimmunity, CXCR5+CD8 T cells are implicated in disease progression. During viral infection and cancer, CXCR5 expression on CD8 T cells generally is indicative of progenitor memory stem-like exhausted cells, which are more responsive to immune checkpoint blockade therapy. The use of immune checkpoint inhibitors to overcome immune exhaustion in cancer, and subsequent consequence of immune adverse events, highlights the dual nature of the cellular immune response. This review will detail the functionality of CXCR5+CD8 T cells in cancer and autoimmunity with potential repercussions during immune checkpoint blockade therapy discussed.